Arrival city. Invisible diversity at Prague's housing estates. - Hermanová, Marie; Lehecka, Michal (Steiner, 2019)
After 1989, socialist modernist cities in Prague have undergone significant changes in their neighbourhood structure. How does international migration (especially from eastern Europe) change the public space and everyday live in the housing estates in Prague's Southwest city?
Keywords: Stadtentwicklung; Urbanität; Verstädterung; Migration; Bevölkerungswanderung; Zuwanderung; Wanderungsbewegung; Wohnsiedlung; Großsiedlung; Heterogenität; Bewohner; Stadtraum; Lokale Identität; Ausstellung